Victorian Life - Guy, John (Tunbridge Wells Ticktock, 1997)
Suitable for National Curriculum History Key Stage 2/3, a SNAPPING TURTLE GUIDE which reveals what life was like in the time of Queen Victoria, showing how social and technological changes also brought poverty and misery for many. Illustrated with colour artwork.
Include Illustrations, Glossary and Index.
Keywords: Great Britain -- Social conditions